Vertigo: A single Institutional Experience - Sabir Saeed , Aso (Diyala Journal of Medicine, 2020)
Background: Vertigo is an illusion or hallucination of movement, often horizontal and rotatory, either of oneself or the environment. The type is either central or peripheral, but sometimes it cannot be identified. Objective: We analyzed the etiologies of peripheral and central vertigo in our patients. Patients and Methods: The cross-sectional observational study enrolled 100 patients consecutively, who had attended the Rizgary Teaching Hospital’s neurology outpatients’ clinic in Erbil, Iraq, from January 1, 2019, to October 31, 2019. Thorough history, full general and neurological examinations and an extensive battery of investigations (including cranial contrast MRI) were performed. Patients with peripheral vestibulopathy and vertigo were assessed by otolaryngologists. Results: Females (69%) outnumbered males (31%). Patients in their 6th decade were the commonest target; the mean age was 46.7 years. Peripheral vertigo was evident in 46% of the patients while central vertigo occurred in 36% of them. In 18% of the patients, no cause was identified; most of them were females (88.8%) in their 7th decade of age. Benign paroxysmal positional vertigo (BPPV) dominated the peripheral vertigo cases. The most prevalent cause of central vertigo was vertebrobasilar insufficiency (VBI) (27%); many were above 50 years of age. Conclusion: Peripheral vertigo was more prevalent than the central ones. BPPV and VBI were the commonest causes of vertigo, in general. Vertigo mainly targeted middle-aged individuals in our city.